Effects of elevated seawater pCO2 on the blue mussel Mytilus edulis - Casties, Isabel (2011)
Due to rising atmospheric carbon dioxide concentrations, the oceans take up more CO2 resulting in a decrease of seawater pH. This effect is called ocean acidification. Already today, low pH values can be encountered in Kiel Fjord during summer, when COrenriched bottom water is upwelled to the surface. In the present study, recently settled Mytilus edulis were grown for 7 weeks under experimental conditions. The effect of 4 pCO2 treatments (control=380, 1120, 2400, 4000 μatm) in combination with 3 different feeding levels (low, medium, high) of Rhodomonas sp. cells on mussel growth was measured. Low food supply had a larger negative impact on shell length growth than elevated pC02 (hypercapnia), while high nutritional supply could compensate a negative effect of hypercapnia. In the 4000 μatm group, mussels reached a mean length of about 1301 ± 75 μm and 3380 ± 677 μm under low and high feeding conditions, respectively. No differences in the length-dry mass ratio were detected, but high pCO2 (4000 μatm) incubated shells contained significantly more organic and less calcium carbonate. The organic content increased to 13-15.6 % compared to 11.5-13 % of shell dry mass in the control treatment. Since the organic part of the shell and the body somatic tissue make up similar fractions of total organic mass, shell formation was associated with high energetic costs. 43-84 % of the energy uptake in the low and 33-46 % in the high feeding group accounted for energy that was used for growth processes (somatic and shell). Mussels of the intermediate feeding group used 23-63% of the energy input for growth, with lowest values under highest hypercapnia. The remaining energy fraction was used in respiration and excretion. These parameters were also measured and displayed high fluctuations, which might be due to methodical problems. The results of the study support the view that Mytilus edulis populations can cope with the near future predicted ocean acidification when enough food is available.